The Effectiveness of Combination of Yam Bean and Tomato Juices Againts Sugar Levels of Diabetics Militus Patients Type 2 - Hasneli Hasneli; Andrafikar Andrafikar; Apreriza Putri (Jurnal Sehat Mandiri, 2018)
Diabetics militus is a group of metabolic diseases with hyperglichemic that is caused by abnormality insulin secretion, insulin works, or both of them. One of alternative for decreasing sugar levels is yam bean and tomato juices consumption. The aim of the research is to exposed the influence of yam bean juice and tomato juice againts sugar levels of diabetics militus type 2. This research is experimental study with pretes-posttest with control group design. We used purposive sampling with 18 respondenses. The primary data are intake interview, IMT measurement, and blood sugar levels. And the secondary data are the data resources about diabetics militus. Data are analyzed statically by T-test two mean differences dependent and independent with error degree 5%. The result showed that the avarage of sugar blood levels before and after intervension respectively is 287,6 mg/dl and 220,8 mg/dl. There was the significant difference between blood sugar levels before and after group cases (p<0,05). The avarages of blood sugar levels before and after intervension on control’s group respectively are 317,8 mg/dl and 331,9 mg/dl. There was no significant difference of blood sugar levels in the begining and final of control’s group (p<0,05). There was an influence of yam bean juice and tomato juice supply againts blood sugar levels at a time (p<0,05). This study is expected to suggest the people with diabetes mellitus to consume yam bean and tomato juice as an alternative way to control or to decrease blood level sugar.